Transparansi dan Akuntabilitas Pelaporan Keuangan Lembaga Keuangan Syariah di Indonesia: Perspektif Islam dan Pemangku Kepentingan - Ismadharliani, Aztyara; Anggraini, Dessy; Irawan, Anja (Program Studi Manajemen Keuangan Syariah, 2026)
This study aims to analyze the transparency and accountability of financial reporting in Islamic financial institutions (IFIs) in Indonesia from the perspectives of Islam and stakeholders. Transparency and accountability are fundamental principles in Islamic financial management that serve to uphold trust (amanah), enhance public confidence, and ensure compliance with Sharia principles. This study employs a descriptive qualitative approach with a case study design involving several Islamic financial institutions in Indonesia. Data were collected through in-depth interviews with the management of Islamic financial institutions, analysis of financial statement documents, and a review of relevant literature. The findings indicate that the practices of transparency and accountability in the financial reporting of Islamic financial institutions in Indonesia have shown considerable improvement, particularly in terms of compliance with Sharia accounting standards and the disclosure of basic financial information. Nevertheless, several challenges remain, including limitations in human resource capacity, variations in the understanding of Sharia accounting standards, and the suboptimal disclosure of non-financial information such as social impact and Sharia compliance. This study provides important implications for strengthening Islamic financial management practices and for formulating policies aimed at improving the quality of Sharia financial reporting in Indonesia.